Overview of instrumentation used in endodontics - Alharbi, Yazeed Mohammad; Alharby, Amjad Ghalib; Alyami, Abdullah Mahdi; Salem, Rahaf Abdulkhaliq; Alghamdi, Saeed Ali; Alrabiah, Abdullah Mohammed; Alsakran, Huda Abdullah; Alorabi, Abdullah Abed; Jad, Yaser Ali; Zarei, Lamees Annas; Alshehri, Layan Saad (International Journal Of Community Medicine And Public Health, 2022)
The fundamentals of root canal therapy include thorough cleaning, suitable shape, and total root canal filling. There are numerous tools at our disposal to help us achieve these goals. A complicated range of files, filling techniques, and modern materials have been designed to speed up the process, increase its dependability, and enable the clinician to properly treat challenging patients and intricate anatomies. Hand instruments include barbed broaches, reamers, and files such as K-file, K-flex file, Flexofile, and Hedstrom files. Nickel-titanium alloys have been used to replace stainless steel in the production of endodontic equipment. Compared to stainless steel tools, these lead to more straightening of canal curvature, centering, tapering, and leading to a superior preparation. In an effort to speed up preparation of canals and lessen operator fatigue, a wide variety of electric power-run tools have been created like reciprocating handpieces, rotary NiTi files and handpieces. Accurate root canal length measurement is crucial to the effectiveness of root canal therapy. Radiography and the application of an electronic apex locator are the two methods used most frequently to confirm canal length. Instruments needed for filling canals are dependent on the procedure chosen to fill the root canal. Hand or finger spreader with a pointed tip are used in lateral condensation; hand or finger pluggers with blunt, flat ends are employed in vertical condensation; thermomechanical compaction uses an engine-powered compactor, thermoplasticized injectable gutta-percha and gutta-percha carrier devices. Careful use of canal preparation, sterilization, and obturation techniques, together with the appropriate instrument selection and use, can significantly increase the likelihood that endodontic procedures will be successful.